Graves’ disease patients who relapsed are twice as likely to become euthyroid following low dose carbimazole treatment compared to radioiodine therapy - Joseph Anthony Abdullah, Muhd Mikhail; Shahar, Mohammad Arif; A. Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine & Metabolic Society, 2016)
Background: The use of low dose antithyroid treatment for relapsed Graves’ Disease has recently been considered a possible viable alternative to ablative therapies such as radioiodine or thyroidectomy.